Acts and the Historical Monograph - Palmer, Darryl W. (Tyndale bulletin, 1992)
Despite other recent suggestions, Acts deserves consideration as a ‘historical monograph’. The modern phrase denotes a historical writing, which deals with a limited issue or period and may also be limited in length. In ancient discussion Polybius contrasts the historical monograph with his universal history. Sallust writes Roman history ‘selectively’. Cicero’s correspondence reveals his concept of various features of the historical monograph. Acts qualifies as a short historical monograph: it deals with a limited issue and period in a single volume; and, like Sallusts’s historical monographs, contains a prologue, narrative, speeches, quoted letters and even a historical survey. The subject-matter is unprecedented.